A new organic compound of 2-(2, 2-diphenylethenyl)anthracene (DPEA) showing simultaneous electrical charge transport property and AIE optical characteristics. Issue 15 (28th March 2018) - Liu, Dan; Li, Jie; Liu, Jie; Lu, Xiuqiang; Hu, Mengxiao; Li, Yang; Shu, Zhibin; Ni, Zhenjie; Ding, Shang; Jiang, Lang; Zhen, Yonggang; Zhang, Xiaotao; et al.
Abstract : DPEA shows good charge carrier mobility and AIE efficient luminescence. Abstract : A new compound, 2-(2, 2-diphenylethenyl) anthracene (DPEA), was designed and synthesized, which showed a hole carrier mobility of 0.66 cm 2 V −1 s −1 and typical aggregated induced emission (AIE) behaviour with a ratio of 15 times, which is among the best performance of recently reported semiconducting AIE materials. This work not only enriches the AIE electronic material systems, but also initiates a new direction for developing high performance integrated optoelectronic organic semiconductors for potential multifunctional applications.